Stable core virome despite variable microbiome after fecal transfer. (4th May 2017) - Broecker, Felix; Russo, Giancarlo; Klumpp, Jochen; Moelling, Karin
ABSTRACT: We recently described the 4.5-year time course of the enteric bacterial microbiota and virome of a patient cured from recurrent Clostridium difficile infection (rCDI) by fecal microbiota transplantation (FMT). Here, we extended the virome analyses and found the patient's phage population to exhibit highly donor-similar characteristics following FMT, which remained stable for the whole period tested (up to 7 months). Moreover, the detected viral populations of donor and patient exhibited comparable diversity and richness. These findings were unexpected since enteric viromes are normally highly variable, assumed to influence the bacterial host community and change with environmental conditions. In contrast to the virome, the bacterial microbiota varied indeed for more than 7 months with ongoing dysbiosis before it reached donor similarity. Our findings that are based on sequence information and protein domain analysis seem to suggest that stable phage properties correlate with successful FMT better than the changing bacterial communities. We speculate that we here preferentially detected a stable core virome, which dominated over a variable flexible virome that may have been too heterogeneous for experimental detection or was underrepresented in the databases. It will be interesting to analyze whether the enteric virome allows predictions for the clinical outcome of FMT for rCDI and other diseases such as inflammatory bowel disease or obesity.